The level and influencing factors of quality of life in patients with brachial plexus injury - Jie Shen; Zhi-Wen Wang (Elsevier, 2014)
Purpose: To investigate the overall quality of life level and identify influencing factors in patients with traumatic brachial plexus injury. Methods: One hundred three patients with brachial plexus injury were assessed using the World Health Organization Quality of Life-BREF (WHOQOL-BREF) and Family Adaptability and Cohesion Evaluation Scale (FACESII-CV) questionnaires. Results: The overall quality of life score from patients with brachial plexus injury was 65.78 ± 15.2. The scores for the physical, psychological and environmental factors were significantly lower than the norm (Ps < 0.05). Regression analysis showed that age, injury located ipsilateral to the dominant hand, upper limb function score, score of family intimacy and family income were all factors influencing the of quality of life. Conclusions: A brachial plexus injury significantly compromises an individual's quality of life. Multiple factors influence this quality, which should be targeted to augment the physical and psychological care provided.